Strategi Penjadwalan Penggantian Roll Pada Mesin Rolling Mill Di PT. Z - Martina De Pores Rio Gani; I Nyoman Lokajaya (Jurnal Kendali Teknik dan Sains, 2023)
PT. Z is one of the companies that produces steel plates located in Surabaya, East Java. Production process at PT. The Z fully uses machines that operate 24 hours a day. The bottleneck in the steel plate production process is that there are often breakdowns caused by people, machines, and materials. In the engine factor, there is often a machine breakdown that makes production stop. The smooth running of the production process is disrupted due to damage to the production machine. High downtime often occurs due to repairs and replacement of components in certain machine parts. Therefore the machine needs maintenance / maintenance (maintenance). Among all production machines, rolling mill machines are the machines with the highest downtime rates. The components in the rolling mill machine that cause the highest downtime of 12,851 minutes are roll components. This study intends to make a scheduling plan for roll replacement on rolling mill machines. The methodology used in this study is Preventive Maintenance by calculating its reliability and making a schedule for replacing and maintaining the machine. The results showed that the average roll replacement every 6 days with 63.21% reliability, and the average roll replacement process time was 131 minutes.